THE IMPACT OF DEVOLUTION OF EDUCATION ON NATIONAL UNITY OF PAKISTAN: A CASE STUDY OF 18TH AMENDMENT - Israrud Din (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the impact of the 18th Amendment's devolution of education on Pakistan's national unity. It aims to assess how decentralization influences national identity amidst diverse political dynamics and potential provincial biases. Using qualitative analysis of primary and secondary data sources, the study employs critical thinking methods to explore the causal relationship between education decentralization and its effects on national unity. Decentralization, as mandated by the 18th Amendment, challenges Pakistan's national unity by prioritizing provincial interests over a cohesive national identity. The dominance of local politics fragments educational priorities, hindering efforts to foster a unified national ethos. Policymakers should engage in inclusive dialogue to reconcile provincial autonomy with national cohesion, strengthen inter-provincial cooperation, and prioritize initiatives promoting a shared national identity through education to mitigate divisive tendencies.